1984
DOI: 10.1111/j.1464-410x.1984.tb06143.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alum to Control Intractable Vesical Haemorrhage

Abstract: Eight patients with hitherto uncontrollable vesical bleeding were treated by irrigating the bladder with a 1% solution of alum. The method does not require anaesthesia and bleeding ceased in every case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…Kennedy et al [41]reported their experience with intravesical alum in 8 patients (7 of whom had received prior radiotherapy for bladder cancer), all of whom continued to bleed after cystodiathermy. A 1% solution of alum was used without anaesthesia.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Kennedy et al [41]reported their experience with intravesical alum in 8 patients (7 of whom had received prior radiotherapy for bladder cancer), all of whom continued to bleed after cystodiathermy. A 1% solution of alum was used without anaesthesia.…”
Section: Treatmentmentioning
confidence: 99%
“…Associated aluminium toxicity may [43, 44]or may not occur [41, 44]. Toxicity is manifested as severe encephalopathy, and while this may be reversible, in some cases it is believed to have been a contributing factor in the subsequent death of the patient [44].…”
Section: Treatmentmentioning
confidence: 99%
“…Also, it is known that alumin salts can cause severe allergic reactions in susceptible individuals even after topical use. 16,17 Formalin instillation, one of the most effective treatments for severe HC, requires general anesthesia and is associated with important long-term complications including fibrosis of the bladder, urinary incontinence, papillary necrosis, vesicouretheral reflux and urinary tract obstruction with hydronephrosis. 18,19 Prostaglandins have been reported to have some beneficial effects when administered intravesically.…”
Section: Discussionmentioning
confidence: 99%
“…In early work, eight patients aged 57-82 years and with severe vesical bleeding had irrigation for a mean of 3 days; the bleeding stopped in all of them within this time [37].…”
Section: Intravesical Alum Irrigationmentioning
confidence: 99%